Tomato UDP-Glucose Sterol Glycosyltransferases: A Family of Developmental and Stress Regulated Genes that Encode Cytosolic and Membrane-Associated Forms of the Enzyme - Ramirez-Estrada, Karla; Castillo, Nídia; Lara, Juan A.; Arró, Monserrat; Boronat, Albert; Ferrer, Albert; Altabella, Teresa (Frontiers in Plant Science, 2017)
Sterol glycosyltransferases (SGTs) catalyze the glycosylation of the free hydroxyl group at C-3 position of sterols to produce sterol glycosides. Glycosylated sterols and free sterols are primarily located in cell membranes where in combination with other membrane-bound lipids play a key role in modulating their properties and functioning. In contrast to most plant species, those of the genus Solanum contain very high levels of glycosylated sterols, which in the case of tomato may account for more than 85% of the total sterol content. In this study we report the identification and functional characterization of the four members of the tomato (Solanum lycopersicum cv Micro-Tom) SGT gene family. Expression of recombinant SlSGT proteins in E. coli cells and N. benthamiana leaves demonstrated the ability of the four enzymes to glycosylate different sterol species including cholesterol, brassicasterol, campesterol, stigmasterol and -sitosterol, which is consistent with the occurrence in their primary structure of the putative steroid-binding domain found in steroid UDP-glucuronosyltransferases and the UDP-sugar binding domain characteristic for a superfamily of nucleoside diphosphosugar glycosyltransferases. Subcellular localization studies based on fluorescence recovery after photobleaching and cell fractionation analyses revealed that the four tomato SGTs, like the Arabidopsis SGTs UGT80A2 and UGT80B1, localize into the cytosol and the PM, although there are clear differences in their relative distribution between these two cell fractions. The SlSGT genes have specialized but still largely overlapping expression patterns in different organs of tomato plants and throughout the different stages of fruit development and ripening. Moreover, they are differentially regulated in response to biotic and abiotic stress conditions. SlSGT4 expression increases markedly in response to osmotic, salt and cold stress, as well as upon treatment with abscisic acid and methyljasmonate. Stress-induced SlSGT2 expression largely parallels that of SlSGT4. On the contrary, SlSGT1 and SlSGT3 expression remains almost unaltered under the tested stress conditions. Overall, this study contributes to broaden the current knowledge on plant SGTs and provides support to the view that tomato SGTs play overlapping but not completely redundant biological functions involved in mediating developmental and stress responses.